Dietary supplementation of Eucommia leaf extract to growing-finishing pigs alters muscle metabolism and improves meat quality - Zhenglei Shen; Chuxin Liu; Chuangye Deng; Qiuping Guo; Fengna Li; Qingwu W. Shen (Animal Bioscience, 2024)
Objective The objective of this study was to investigate the influence of dietary supplementation of Eucommia ulmoides leaf extract (ELE) on muscle metabolism and meat quality of pigs with and without pre-slaughter transportation. Methods In a 43-day feeding experiment, a total of 160 pigs with an initial body weight 60.00±2.00 kg were randomly assigned into four groups in a completely randomized design with 10 replicates. Pigs in groups A and C were fed a basal diet and pigs in groups B and D were fed a basal diet supplemented with 0.5% ELE. Pigs were slaughtered with (group B and D) or without (group A and C) pre-slaughter transport. Muscle chemical composition, postmortem glycolysis, meat quality and muscle metabolome were analyzed. Results Dietary ELE supplementation had no effect on the proximate composition of porcine muscle, but increased free phenylalanine, proline, citruline, norvaline, and the total free amino acids in muscle. In addition, dietary ELE increased decanoic acid and eicosapentaenoic acid, but decreased heptadecanoic acid, oleic acid, trans-oleic acid, and monounsaturated fatty acids in muscle. Meat quality measurement demonstrated that ELE improved meat water holding capacity and eliminated the negative effects of pre-slaughter transport on meat cooking yield and tenderness. Dietary ELE reduced muscle glycolytic potential, inhibited glycolysis and muscle pH decline in the postmortem conversion of muscle to meat and increased the activity of citrate synthase in muscle. Metabolomics analysis by liquid chromatographic tandem mass spectrometric showed that ELE enhanced muscle energy level, regulated AMP-activated protein kinase (AMPK) signaling, modulated glycogenolysis/glycolysis, and altered the metabolism of carbohydrate, fatty acids, ketone bodies, amino acids, purine, and pyrimidine. Conclusion Dietary ELE improved meat quality and alleviated the negative effect of pre-slaughter transport on meat quality by enhancing muscle oxidative metabolism capacity and inhibiting glycolysis in postmortem muscle, which is probably involved its regulation of AMPK.